A Comparison of 940 nm Diode Laser and Cryosurgery With Liquid Nitrogen in the Treatment of Gingival Physiologic Hyperpigmentation Using Split Mouth Technique: 12 Months Follow Up - Jokar, Leila; Bayani, Mojtaba; Hamidi, Hamid; Keivan, Mohammad; Azari-Marhabi, Saranaz (Journal of Lasers in Medical Sciences, 2019)
Introduction: Gingival hyperpigmentation is excessive deposition of melanin pigments in the epithelium of gingiva which affects facial esthetics. Various surgical methods for gingival depigmentation have been used to treat the darkened color of pigmented gingiva. This study compared the use of 940 nm diode laser and liquid nitrogen cryosurgery in the treatment of gingival physiologic hyperpigmentation in terms of gingival depigmentation, postoperative pain, healing duration, pigmentation recurrence, and patients’ satisfaction. Methods: Fifteen systemically healthy patients (11 females and 4 males; 17-35 years of age) with bilateral gingival physiologic hyperpigmentation were enrolled in this split-mouth randomized study. Maxillary anterior labial gingiva of each patient was divided into left and right halves, and each half was randomly depigmented by either laser or cryosurgery. Patients were given questionnaires to evaluate the procedures and were followed up in 3, 7, 10, 17 and 21 days postoperatively for the assessment of gingival healing and 1, 3, 6 and 12 months after the treatments to detect any sign of pigmentation recurrence. Results: The severity of post-op pain measured by visual analogue scale (VAS) was mild to average and showed no significant difference between the 2 modalities (P > 0.05). There was no considerable swelling or hemorrhage after the treatment procedures and the healing duration was significantly shorter in laser (P < 0.05). The degree of pigmentation in all gingival sites treated by laser reached and remained at zero until the last follow up (1 year) and reached zero in 9 out of 15 cryosurgery-treated sites. All patients were completely satisfied with the laser, and 9 out of 15 were completely satisfied with cryosurgery. No pigmentation recurrence was observed during any follow-up periods. Conclusion: Removal of gingival physiologic hyperpigmentation by laser therapy and cryotherapy was effective and safe. The efficiency of the laser was better than cryotherapy.